Artificial ground freezing for underground construction – a brief review of the theory, practice and challenge - Mao, Huan; Huang, Jie; Johnson, Drew W. (Frontiers in Built Environment, 2024)
Since Artificial ground Freezing (AGF) appeared in the 1880s in the mining sector in Europe, it has been used for various construction applications worldwide. In recent years, it has been increasingly popular in urban projects due to its versatility and applicability to complicated site conditions. So far, it has been used to stabilize substrata to nearly 1,000 m below the ground surface, which is considered not possible for many other ground improvement technologies. Due to the growth in field applications, the practice and theories related to AGF have become more mature in the most recent two decades. The improvement in understanding of this topic is a result of lessons that have been learned through numerous projects, as well as a variety of comprehensive studies that have been completed. This paper reviews the existing practice, the recent development on AGF and the challenges of AGF.